Foundations of aural rehabilitation : children, adults, and their family members - Tye-Murray, Nancy (Plural Publishing, 2020)
"Foundations of Aural Rehabilitation: Adults, Children, and Their Families, Fifth Edition, introduces the fundamentals of audiologic rehabilitation and hearing-related speech-language pathology in an easy-to-read, concise resource for the field of communication sciences and disorders. The text offers creative coverage of theory, clinical practice, and research-based approaches for identifying, diagnosing, and treating hearing and communication-based disorders. The text is separated into three sections for the most comprehensive coverage of each topic: Part 1 describes the components of an aural rehabilitation plan, Part 2 concerns adults and their family members, and Part 3 concerns children and their parents. Important topics throughout include patient-centered services, counseling, selection and fitting of listening devices, conversational fluency and communication strategies training, auditory training, speechreading, and language and speech acquisition"--Publisher's description